Brush border membrane vesicle purification using andean potato weevil (premnotrypes vorax hustache) epithelial midgut tissue (2002)
The use of micro-organisms as biological pest control agents requires basic studies related to their action mechanism inside the target insect. Brush border membrane vesicles (BBMVs) obtained from different insects' epithelial gut tissues have become a valuable tool worldwide in action mechanism studies employing Bacillus thuringiensis, which is considered to be the micro-organism most used for biological pest control in agriculture throughout the world. This work's objective was to standardise a BBMV purification methodology using Andean potato weevil gut tissues for use in further studies with coleopteran B. thuringiensis proteins, exploring their potential in turn as P. vorax biological control agents. This work was carried out with P. vorax late stage larvae, obtained from a laboratory colony. BBMVs purification methodology was standardised by using a basic methodology developed by Wolfersberger et al (1987). BBMVs were characterised by SDS PAGE and electrón microscopy analysis. Total protein present was also quantified. A BBMV purificate was obtained, having vesicles with size and shape similar to others reported in the international literature. Average total protein was 1 mg/ml, this being suitable for B. thuringiensis protein binding assays. BBMV SDS PAGE analysis showed a protein complex with proteins ranging from 24 KDa to 116 KDa. Nowadays, BBMV purification methodology is being used in B thuringiensis protein binding studies with brush border receptors present in Andean potato weevil gut.